2017
DOI: 10.1021/acs.biochem.7b01036
|View full text |Cite
|
Sign up to set email alerts
|

Reshaping the Energy Landscape Transforms the Mechanism and Binding Kinetics of DNA Threading Intercalation

Abstract: Molecules that bind DNA via threading intercalation show high binding affinity as well as slow dissociation kinetics, properties ideal for the development of anticancer drugs. To this end, it is critical to identify the specific molecular characteristics of threading intercalators that result in optimal DNA interactions. Using single-molecule techniques, we quantify the binding of a small metal-organic ruthenium threading intercalator (Δ,Δ-B) and compare its binding characteristics to a similar molecule with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…SMFS study can provide deep insight into binding kinetics and the magnitude of the double helix structural deformations during the assembling of DNA-ligand complexes at a single molecule level, which is the major advantage over other techniques [29,58,59,60,61,62,63,64,65,66]. Before the use of this technique, the self-assembly process of DNA-intercalator complex molecules had been investigated via different experimental means such as thermal denaturation and stopped-flow techniques, which were employed to explore the first kinetics studies of DNA intercalation [67,68].…”
Section: Single Molecule Force Spectroscopy Studymentioning
confidence: 99%
See 1 more Smart Citation
“…SMFS study can provide deep insight into binding kinetics and the magnitude of the double helix structural deformations during the assembling of DNA-ligand complexes at a single molecule level, which is the major advantage over other techniques [29,58,59,60,61,62,63,64,65,66]. Before the use of this technique, the self-assembly process of DNA-intercalator complex molecules had been investigated via different experimental means such as thermal denaturation and stopped-flow techniques, which were employed to explore the first kinetics studies of DNA intercalation [67,68].…”
Section: Single Molecule Force Spectroscopy Studymentioning
confidence: 99%
“…Higher forces facilitated the intercalative binding, which led to a profound decrease in the binding site size, and resulted in one ligand intercalation at almost every DNA base stack. The force-dependent kinetics analysis revealed a mechanism that requires a DNA elongation of 0.33 nm for association, relaxation to an equilibrium elongation of 0.19 nm, and an additional elongation of 0.14 nm from the equilibrium state for dissociation [66,83]. They also reported that a ruthenium dimer complex with a flexible linker slowly threads between the DNA bases in two distinct steps under a constant applied force; the results showed that the ligand association was described by a two-step process, which consists of a fast-bimolecular intercalation of the first dppz moiety, followed by a 10-fold slower intercalation of the second dppz moiety.…”
Section: Single Molecule Force Spectroscopy Studymentioning
confidence: 99%
“…Conversely, small-molecule binding to DNA can alter its structure and mechanical properties. Specifically, intercalation lengthens and unwinds the DNA helix (7,8), and the changes upon intercalation into DNA have been investigated at the single-molecule level using optical tweezers (3,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21), AFM force spectroscopy (22,23), and magnetic tweezers (MT) (24)(25)(26)(27). In contrast, minor groove binding has only much smaller effects, if any, on DNA length and winding angle (24).…”
Section: Introductionmentioning
confidence: 99%
“…While only a limited attention has been focused on the DNA binding studies of dinuclear Ru(II) complexes. [6,10,[11][12][13][14][15][16][17][18][19][20][21][22] A dinuclear Ru(II) complex [{(bpy) 2 Ru} 2 (4-azo)] 4+ {bpy = 2,2′-bypyridine), 4-azo = 4,4′′-azobis(2,2′-bipyridine)} was found to groove binds to DNA and functions as a colorimetric sensor for different sequence and structure of DNA. [21] Complexes of [μ-bidppz(phen) 4 Ru 2 ] 4+ {bidppz = 11,11′-bi(dipyrido[3,2a:2′,3′-c]phenazinyl)} and [μ-dppzip(phen) 4 Ru 2 ] 4+ {dppzip = 2-(dipyrido[3,2a:2′,3′-c]phenazin- 11-yl)imidazo [4,5-f] [1,10]phenanthroline)} display unusual threading intercalation interaction with DNA.…”
Section: Introductionmentioning
confidence: 99%
“…[22] It is noteworthy that of the dinuclear Ru(II) complexes reported, many of them have been shown to bind to DNA through threading monointercalation, or threading bis-intercalation. [9,[11][12][13][14][15][16][17][18][19][20] We have put much attention on DNA intercalation for dinuclear Ru(II) complexes, while only a few dinuclear Ru(II) complexes have been reported to groove bind to DNA or partial intercalate to DNA, to the best of our knowledge. [21,22] As with intercalators, groove binders can also be used as chemotherapeutic agents, such as clinical treatment of cancer and bacterial infections, so the groove binding need more exploration for structure-function relationship.…”
Section: Introductionmentioning
confidence: 99%